Utilization of Digital Technology in Children's Education to Enhance Creative and Interactive Learning - Agustina, Ika; Aprina Siregar, Lailan; Liliani Husain, Desy; Asfahani, Asfahani; Pahmi, Pahmi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
The use of digital technology requires creativity and interaction between users. This is to support the implementation of good learning. This study aims to determine the impact of using digital technology in the context of children's learning on increasing creativity and interaction. Researchers used a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis techniques followed the stages of Miles and Humbermen analysis, namely data collection, data reduction, data presentation, and verification. Content analysis and thematic analysis were used to analyze the data collected and identify common and thematic patterns related to the use of digital technology in children's education. The results show that the use of digital technology in children's education has great potential in enhancing creative and interactive learning. Educational games, visual simulations, and interactive multimedia content allow children to think creatively, collaborate, and interact more deeply with learning materials. However, the research also emphasizes the need to balance the use of technology and real social interaction, as well as the selection of developmentally appropriate content. So, the results of this research can be important information for schools that the use of digital technology affects creativity and interaction between teachers and students.